A threat to loyalty: Fear of missing out (FOMO) leads to reluctance to repeat current experiences - Hayran, Ceren; Anik, Lalin; Gürhan-Canli, Zeynep (PLOS ONE, 2020)
We investigate a popular but underresearched concept, the fear of missing out (FOMO), on desirable experiences of which an individual is aware, but in which they do not partake. Through laboratory and field studies, we establish FOMO’s pervasiveness as a psychological phenomenon, present real-life contexts wherein FOMO may be experienced, and explore its behavioral consequences. Specifically, we show that FOMO poses a threat to loyalty by decreasing one’s intentions to repeat a current experience and may decrease the valuation of the current experience.